The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1046/j.1471-4159.2003.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain serotonin synthesis is increased in the olfactory bulbectomy rat model of depression: an autoradiographic study

Abstract: Serotonin synthesis rates were evaluated using a-[ 14 C]methyl-L-tryptophan (a-MTrp) autoradiographic methods in olfactory bulbectomized (OBX) rats. They were significantly (p < 0.05) increased in the frontal (50%) and parietal (40%) cortices, superior olive (over 30%), and the substantia nigra (30%) in the OBX rats as compared to the sham operated animals. There were also increases in 5-hydroxytryptamine (5-HT) synthesis in some limbic areas: the cingulate (32%), the medial forebrain bundle (58%), the hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 65 publications
(80 reference statements)
8
42
2
1
Order By: Relevance
“…39 Studies have also shown that 5-HT 1A receptors are supersensitive in the FSL rats when compared to the SPD controls. 16,17 Further, 5-HT synthesis has been identified as a parameter that is affected by OBX 40,41 and is normalized by antidepressant treatments. 27,41 As noted, we concentrate on the OBX and FSL rat models of depression in this review, because our group has acquired a substantial volume of data on the serotonergic system in these two models, and that data is not available on any other animal model.…”
Section: Skelin Et Al Neurochemical and Behavioural Changes In Rmentioning
confidence: 99%
See 2 more Smart Citations
“…39 Studies have also shown that 5-HT 1A receptors are supersensitive in the FSL rats when compared to the SPD controls. 16,17 Further, 5-HT synthesis has been identified as a parameter that is affected by OBX 40,41 and is normalized by antidepressant treatments. 27,41 As noted, we concentrate on the OBX and FSL rat models of depression in this review, because our group has acquired a substantial volume of data on the serotonergic system in these two models, and that data is not available on any other animal model.…”
Section: Skelin Et Al Neurochemical and Behavioural Changes In Rmentioning
confidence: 99%
“…40,49 In brief, Sprague-Dawley (SPD) rats (weighting 200-250 g) are anaesthetized with inhalatory anaesthetics, isoflurane or halothane, and the small hole is opened on the frontal bone, 5.2 mm anterior from the bregma and approximately 2 mm on both sides from the midline. The olfactory bulbs are visualized with a surgical microscope, cut and aspirated with a dull needle attached to a vacuum water pump, taking care not to damage the frontal lobes.…”
Section: Surgical Procedures and Its Subsequent Neuroanatomical Implicmentioning
confidence: 99%
See 1 more Smart Citation
“…As several reports have linked olfactory bulbectomy to changes in the amygdala and hippocampus (Richardson and Tiong, 1999, elevated density of b-adrenoceptors in the amygdala and hippocampus; Wrynn et al, 2000, decreased MRI signal in the amygdala, indicating an altered tissue volume, pronounced enlargement of the lateral ventricle with impaired hippocampal function as a consequence; Rutkoski et al, 2002, significant increase in neuropeptide Y expression in the amygdala; Watanabe et al, 2003, increased serotonin synthesis in the hippocampus), we selected the two brain areas for this study. Moreover, the hippocampus and amygdala besides the anterior cingulate and the prefrontal cortex are included into the key neural circuit of depression (Henn and Vollmayr, 2004b;Sapolsky, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, a buspirona é utilizada no tratamento da ansiedade. Entretanto, estudos demonstram que pode haver alterações nas funções do sistema serotoninérgico durante a patogê-nese da epilepsia 3,4 , despertando, assim, o interesse na investigação da buspirona em modelos de epilepsia.…”
Section: Introductionunclassified